The Impact of The English Language Speech Assistant (ELSA) Application on Students’ Pronunciation Skills - Nur Fauziah; Zalzabil Zakiah Aororah; Repi Anjani Ramadhany; Sitti Maryam Hamid (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study aims to evaluate the impact of the ELSA Speak app on students' pronunciation learning at Universitas Muhammadiyah Makassar by comparing their performance before and after using the app. This study employed a pre-experimental design, utilizing a post-test and pre-test method with a quantitative approach. The researchers selected 40 students from the English education class A and B of 2023 at the university. A questionnaire was conducted to understand the students' perspectives on their pronunciation skills after undergoing the treatment. The results showed that only 4 students showed a decrease in scores of pre-tests and post-test (negative ranks), whereas 23 participants demonstrated an improvement from the pretest to the posttest. The data from the t-test analysis indicated that most students experienced an increase in pronunciation skills, demonstrating its effectiveness in improving the pronunciation of EFL learners. Additionally, this data shows that the ELSA Speak app has a significant impact on improving pronunciation and also motivation.